Comparing the PRISMA-7 and a Modified Version (PRISMA-6) for Frailty Screening: Addressing Sex Bias in Community-Dwelling Older Adults - Dietmar Ausserhofer; Angelika Mahlknecht; Verena Barbieri; Adolf Engl; Giuliano Piccoliori; Christian J. Wiedermann (Geriatrics)
Background/Objectives: Frailty screening facilitates the identification of older adults at risk of adverse health outcomes. The Program of Research to Integrate Services for the Maintenance of Autonomy 7 (PRISMA-7) is a widely utilised frailty tool; however, concerns regarding its potential sex bias persist due to item 2, which assigns a frailty point for male sex. This study compared the PRISMA-7 with a modified version, the PRISMA-6 (excluding item 2), to assess their suitability for frailty screening in South Tyrol, Italy. Objectives included evaluating the impact of item 2 on frailty classification and exploring the feasibility of the PRISMA-6 as a more equitable alternative. Methods: A cross-sectional survey of 1695 community-dwelling older adults aged ≥75 years was conducted in South Tyrol. Frailty was assessed using both the PRISMA-7 and PRISMA-6. Sociodemographic, health, and lifestyle data were collected to examine associations with frailty classifications. Logistic regression was applied to identify predictors of frailty for each tool. Agreement between the PRISMA-7 and PRISMA-6 was assessed, and internal consistency was evaluated using Cronbach’s alpha. Results: Frailty prevalence was 33.9% with the PRISMA-7 and 27.0% with the PRISMA-6. The PRISMA-7 classified men as frail more frequently than women (34.7% vs. 33.0%), while the PRISMA-6 reversed this trend (men, 21.4%; women, 33.0%). Excluding item 2 improved internal consistency (Cronbach’s alpha: PRISMA-7, 0.64; PRISMA-6, 0.75) and aligned frailty classifications with predictors such as age, health status, and physical activity. Logistic regression revealed significant sex differences with the PRISMA-7 but not with the PRISMA-6. Conclusions: The PRISMA-7 introduces sex bias by overestimating frailty in men, whereas the PRISMA-6 provides a more equitable and consistent alternative. The findings highlight the PRISMA-6’s potential as a reliable tool for unbiased frailty screening. Future research should validate the PRISMA-6 against established frailty tools to support its integration into primary care settings.